MENTAL HEALTH OF CHILDREN AND ADOLESCENTS – AN INTERSECTORAL APPROACH IN THE MUNICIPALITY OF ANÁPOLIS: EXPERIENCE OF THE MEDICAL PROGRAM - Melo, Cecília Magnabosco; Rodrigues, Fábio Fernandes; Silva, Rúbia Mariano do; Usevicius, Priscila Maria Álvares; Major, Cláudia Regina; Sterse, Carlos Limongi; Mesquita, Janete Lopes dos Santos; Silva, Flávia Fernanda de Souza; Lima, Marco Aurélio da Silva; Tavares, Giovana Galvão (CIPEEX, 2025)
Depression and self-harm in children and adolescents are part of the statistics of growing demand for mental health problems worldwide. This study aims to report the experience of the Family and Community Medicine module of the Medicine course at UniEVANGÉLICA in the intersectoral approach to mental health conditions in children and adolescents in the municipality of Anápolis, in 2023 and 2024. Screening for depression and self-harm was carried out among elementary school students, mental health promotion activities were implemented for children and adolescents, and continuing education activities were provided for primary health care teams. As a result, 403 children participated in the screening for depression and self-harm, 11 mental health promotion actions were carried out in schools, and 8 Basic Health Units received continuing education in mental health. It is observed that intersectoral actions between education, health, and social integration become enablers in organizing the absorption of this demand, and the university can contribute with updated scientific references and generate a positive impact on the community in which it is inserted.